Internet deception to share IoC - Maddalena Kreff, Pablo Germán (2025)
The detection of cybersecurity attacks through the collection and analysis of information is a challenge that focuses, in this work, on the use of honeypots, which are decoys that allow attacks to be studied in a controlled environment. The data collected can be used as a source of information in Cyber Threat Intelligence (CTI). Cyber Deception is a form of deception that exploits digital tools to deceive, manipulate or confuse a target, where the value lies in being attacked and investigated. Thus, honeypots constitute a Cyber Deception mechanism. Cybersecurity frameworks provide a reference model for the analysis of attacks, favoring their classification and understanding in order to mitigate them. Furthermore, these frameworks help to understand the stages of attacks linked to Cyber Deception mechanisms, including honeypots. The aim of the work is to analyze the communication mechanisms between honeypots and CTI platforms, with the aim of improving the cybersecurity strategies of organizations.